2003
DOI: 10.1074/jbc.m212754200
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin-2 Determines Mitochondrial Network Architecture and Mitochondrial Metabolism

Abstract: In many cells and specially in muscle, mitochondria form elongated filaments or a branched reticulum. We show that Mfn2 (mitofusin 2), a mitochondrial membrane protein that participates in mitochondrial fusion in mammalian cells, is induced during myogenesis and contributes to the maintenance and operation of the mitochondrial network. Repression of Mfn2 caused morphological and functional fragmentation of the mitochondrial network into independent clusters. Concomitantly, repression of Mfn2 reduced glucose ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
678
1
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 758 publications
(743 citation statements)
references
References 51 publications
52
678
1
12
Order By: Relevance
“…Mfn2 can also interact directly with Ced9 or BclxL in HEK293 cells suggesting a mechanism for crosstalk with antiapoptotic Bcl family proteins [71]. Mfn2 has been shown to modulate metabolism [104,105] and cell cycle [106]. We therefore suggest that Mfn2, unlike Mfn1, may be able to provide additional protection against neuronal apoptosis through mitochondrial fusion independent mechanism, such as metabolic and cell cycle control (Fig.…”
Section: The Role Of Mitochondrial Fusion In Cell Death: Mfn1 and Mfnmentioning
confidence: 89%
See 1 more Smart Citation
“…Mfn2 can also interact directly with Ced9 or BclxL in HEK293 cells suggesting a mechanism for crosstalk with antiapoptotic Bcl family proteins [71]. Mfn2 has been shown to modulate metabolism [104,105] and cell cycle [106]. We therefore suggest that Mfn2, unlike Mfn1, may be able to provide additional protection against neuronal apoptosis through mitochondrial fusion independent mechanism, such as metabolic and cell cycle control (Fig.…”
Section: The Role Of Mitochondrial Fusion In Cell Death: Mfn1 and Mfnmentioning
confidence: 89%
“…In the following section we will discuss the mitochondrial fusion independent role of Mfn2 in metabolism, cell cycle control and apoptosis. Studies in diabetic model systems have indicated that the reduction of Mfn2 leads to an inhibition of glucose oxidation and cell respiration, which is linked to obesity in both rat and human [104]. Mfn2 control of metabolism is not dependent on mitochondrial fusion, since expression of a truncated form of Mfn2 that is localized in cytoplasm can still increase mitochondrial respiration.…”
Section: The Role Of Mitochondrial Fusion In Cell Death: Mfn1 and Mfnmentioning
confidence: 99%
“…However, while this investigation found no changes in apoptosis in DOX‐treated HL‐1 cardiomyocytes in the presence of Nox2 or Mfn2 knockdown, it is possible that efficacy of transfection may have influenced the measured endpoint. Indeed, highly oxidative tissues such as the heart require constant energy production, and as mitochondria are the powerhouse of the cardiomyocyte comprising a large proportion of cytoplasmic volume, it is possible that there is such a high level of Mfn2 expression in HL‐1 cardiomyocytes that the observed effects of Mfn2 siRNA on cell apoptosis may have underestimated the involvement of Mfn2 (Bach et al, 2003; Papanicolaou et al, 2011). Indeed, when a higher level of knockdown was achieved, a lack of Mfn2 corresponded with reduction of caspase 3/7 activity, assessed by both DEVD and PARP‐1 cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Mfn2 expression is ubiquitous in mammalian tissues, albeit it finds its highest expression levels in tissues enriched in mitochondria, such as heart and the brown adipose tissue (BAT) (Bach et al , 2003). Recently, the BAT has gained significant attraction after its identification and localization in humans (for review, see Peirce et al , 2014).…”
Section: Introductionmentioning
confidence: 99%